A peptide antagonist of F11R/JAM-A reduces plaque formation and prolongs survival in an animal model of atherosclerosis. (May 2019) - Babinska, Anna; Clement, Cristina C.; Przygodzki, Tomasz; Talar, Marcin; Li, Yan; Braun, Marcin; Wzorek, Joanna; Swiatkowska, Maria; Ehrlich, Yigal H.; Kornecki, Elizabeth; Watala, Cezary; Salifu, Moro O.
Abstract: Background and aims: The F11 Receptor (F11R), AKA Junctional Adhesion Molecule-A (JAM-A) (F11R/JAM-A), is an adhesion protein constitutively expressed on the membrane surface of circulating platelets and the luminal surface of inflamed endothelial cells (EC). Platelet adhesion to an inflamed endothelium is one of the early steps of atherosclerotic plaque formation. Our previous studies, conducted with cultured EC in vitro, have demonstrated the expression of F11R/JAM-A on the luminal surface of inflamed EC, platelet adhesion to inflamed EC through F11R/JAM-A interactions, and inhibition of this interaction by the presence of F11R/JAM-A antagonistic peptide (F11Rpeptide 4D). In the present study, we examined in vivo the overall health-benefits and cardiovascular effects of long-term treatment of animals prone to atherosclerosis, ApoE −/− mice, with F11R-peptide 4D. Methods: Twenty ApoE −/− mice were assigned to daily treatment with peptide 4D and compared to their counterparts control untreated mice. Mice were observed for wellness and survival. Plaque size in the aorta and heart was measured using histological analysis. Effects of peptide 4D (or scramble control) on platelet adhesion to inflamed endothelium were measured using intravital microscopy. Results: Significant reductions in atherosclerotic plaques number and size, an overall robust health with longer survival were found in the peptide 4D treated group of ApoE −/− mice. Intravital microscopic studies conducted in exposed vessels of ApoE −/− mice demonstrated significant inhibition by peptide 4D of platelet adhesion to the cytokine-inflamed endothelium. Conclusions: Our results demonstrate that peptide 4D significantly reduces atherosclerotic plaque formation in ApoE −/− mice and inhibits platelet adhesion to the inflamed arterial endothelium. Graphical abstract: Image 1 Highlights: We examined effects of F11R derived peptide 4D (P4D) on cardiovascular health and atherosclerotic plaque of ApoE -/- mice. The F11R peptide 4D reduced plaque formation and prolonged survival with overall better health in ApoE -/- mice. P4D inhibited adhesion of platelets to cytokine-inflamed aortic endothelium in ApoE -/- mice shown by intravital microscopy. P4D represents a potential drug for the prevention and treatment of thrombosis and atherosclerosis triggered by inflammation.